Optimalisasi Layanan dan Keamanan: Studi Atas Implementasi Mobile Banking di Era Digital - Andni, Riyan; Sattar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to identify challenges in implementing mobile banking services and security at Bank Rakyat Indonesia. The large number of customer complaints has become an encouragement for researchers, with the hope that the results of this research can help improve the quality of mobile banking features to meet customer satisfaction. The research method used is a qualitative method with a field study approach. The research results show that advances in technology and information, especially mobile banking applications, have become significant progress in the banking sector. Mobile banking is a digital financial service in the form of an application that helps bank customers easily carry out banking transactions via smartphone. Using this application makes it easier for customers to carry out transactions anytime and anywhere without having to visit a bank office. However, there are several disadvantages to using this application, such as potential vulnerability to hackers posing as financial institutions, the need for a stable internet network, the risk of data theft, and the need for a sophisticated smartphone. With this, customers don't need to worry, Bank BRI has implemented a guaranteed security system, obtaining approval from the OJK and the Savings Loan Institution (LPS). BRI mobile banking services are also equipped with biometric security technology through the BRImo application, so users can log in to their BRImo account using fingerprints or facial recognition.